Characterization of foot-and-mouth disease virus gene products with antisera against bacterially synthesized fusion proteins. - Strebel, K (1986)
Defined segments of the cloned foot-and-mouth disease virus genome corresponding to all parts of the coding region were expressed in Escherichia coli as fusions to the N-terminal part of the MS2-polymerase gene under the control of the inducible lambda PL promoter. All constructs yielded large amounts of proteins, which were purified and used to raise sequence-specific antisera in rabbits. These antisera were used to identify the corresponding viral gene products in 35S-labeled extracts from foot-and-mouth disease virus gene products in the nucleotide sequence, to identify precursor-product relationships, and to detect several foot-and-mouth disease virus gene products not previously identified in vivo or in vitro.